Professional perspectives on banking and finance - Choudhry, Moora (Professional perspectives on banking and finance, 2024)
Professional Perspectives on Banking and Finance is a collection of cutting-edge articles written by practitioners for practitioners. Addressing core topics such as risk management, corporate governance, and strategy, but with the emphasis on recent developments and their impact on the industry. These gathered chapters reflect a diverse global outlook, addressing issues of importance and relevance for all bankers. With 100% emphasis on accessible, clear, and applicable advice Professional Perspectives on Banking and Finance provides suggestions to instil best practice in any commercial bank.